PENURUNAN REJECT CLAIM MARKET TERHADAP PLATE BENGKOK PADA BATTERY TYPE YTZ4V DENGAN METODA DMAIC-FAULT TREE ANALYSIS - Fidin Saptaaji; Erry Rimawan (Universitas Mercu Buana, 2017)
Every industry is no exception, the battery industry has a quality standard with priority to reduce reject claims in order to get cost savings and increase consumer confidence. The purpose of this study was to determine the factors causing the high reject claim of bengkok market plate with six sigma (DMAIC) and Fault Tree Analysis (FTA) suppression. The result is a corrective step and standardization to minimize the occurrence of a reject plate group in the future. DMAIC stages include Define, through sampling data collection in Jan-Dec 2016, it is known that the reject claim from Plate Bending is 41 PPM. Step 2 Measure, process reject data and number of claim reject and set improvement targets. Step 3 Analyze, benchmarking cassette A and Cassette B types from the results of FTA analysis, Step 4 Improve, set and standardize changes in dimensions of Cassette Type B by changing the partition part edge L and edge R from C3mm to R4mm from the value of Cp = 1.58, Cpk = 0.63 becomes Cp 2.32 and Cpk 2.23. Step 5 Control, after getting the specified dimensions the value of 29.5 ppm drops to 4 ppm with a target standard of 18 ppm and a decrease in the cost saving of the company is 455.5 KUSD/Year.